Histopathological Review of Skin Diseases: A Three Years Survey of 510 Skin Biopsies in Multan - Sehar Shamshad Ali, Kanwar Sajid Ali, Rozina Kanwar, Hafiz Muhammad Kamran Khalid, Zertaj Kashif, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Skin ailments share a major disease burden worldwide (1, 2).They are considerably frequent in underdeveloped nations and encompass simple ailments like inflammation and pimples to certain grave diseases like skin melanomas (3). However, the type and prevalence of skin disorders differ from area to area on account of dissimilar habitat (4, 5). Skin disorders influence human lives in various ways and many a times the dermal epidermal conditions point some internal ongoing serious disease (6). A vast majority of skin diseases are treated on the basis of clinical diagnosis without confirmation through biopsy. Microscopic examination is mandatory for verification and precise diagnosis and to direct the clinician to opt suitable treatment (7). Considering their importance, the research work being done on the prevalence of specific disorders in particular regions in our country appears deficient especially considering the clinicopathological consonance. The current research was outlined to acumen the skin diseases related burden in our institute. Aim & Objective: The aim of this research is to evaluate the histopathological diversity of skin diseases and their prevalence in Multan region along with the clinic-pathological consonance. Study Design: Retrospective cross sectional study Place and Duration: Histopathology and dermatology departments of Bakhtawar Amin Medical & Dental College and Trust Hospital Multan, from January 2020 to December 2022. Material and Methods: Histopathological reports of all skin biopsies were sorted. The required data like age, gender, clinical presentation, site of the lesion, dermatologist’s findings, and their clinical provisional impression with differential diagnoses were documented along with the histopathological microscopic opinion. The particulars were gathered from clinical files, histopathological demand forms and documented reports. Results: A sum of 510 skin biopsies was received in histopathology section. Out of these, 280 (54.9%) were females and remaining 230 (45.1%) were males. The mean age was 34.70 years (ranging from 2 to 84 years). Most of them were between ages 16-30 years. Majority of the lesions were benign non cancerous and related to skin appendages. Epidermal inclusion cyst appeared to be the most prevalent. Out of 510 biopsies, 68 (13.3%) turned out to be malignant neoplasms. Conclusion: A vast majority of skin diseases are treated only on the basis of clinical diagnosis. The present study revealed that the histopathological opinion was consistent with the clinical judgment in 63 % of the cases, unveiling the significance of histopathological examination that is must for saving time and expenses of the patients. It also helps in reduction of the morbidity related to various skin disorders Keywords: Histopathology, dermatology, skin disorders, skin cancers, epidermal inclusion cyst